2016
DOI: 10.18632/oncotarget.11146
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-specific glycoprotein 9 (PSG9), a driver for colorectal cancer, enhances angiogenesis via activation of SMAD4

Abstract: PSG9 is a member of the pregnancy-specific glycoprotein (PSG) family and has been shown to contribute to the progression of colorectal cancer (CRC) and cancer-related angiogenesis. Here, we aim to investigate abnormal PSG9 levels in patients with CRC and to emphasize the role of PSG9 in driving tumorigenesis. Serum from 140 patients with CRC and 125 healthy controls as well as 74 paired tumors and adjacent normal tissue were used to determine PSG9 levels. We discovered that PSG9 was significantly increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…VEGFA is a member of the PDGF/VEGF growth factor family which encodes a heparin-binding protein that plays predominant roles in angiogenesis by inducing proliferation and migration of vascular endothelial cells. It is upregulated in many known tumors and its expression is correlated with tumor stage and progression (28)(29)(30). Cdc42 is a small GTPase of the Rho-subfamily which regulates cytoskeletal dynamics, cell shape, and numerous other cellular processes including polarity, migration, cell cycle progression and cell fate determination.…”
Section: Snhg15 Affects the Growth Of Glioma Microvascular Endotheliamentioning
confidence: 99%
“…VEGFA is a member of the PDGF/VEGF growth factor family which encodes a heparin-binding protein that plays predominant roles in angiogenesis by inducing proliferation and migration of vascular endothelial cells. It is upregulated in many known tumors and its expression is correlated with tumor stage and progression (28)(29)(30). Cdc42 is a small GTPase of the Rho-subfamily which regulates cytoskeletal dynamics, cell shape, and numerous other cellular processes including polarity, migration, cell cycle progression and cell fate determination.…”
Section: Snhg15 Affects the Growth Of Glioma Microvascular Endotheliamentioning
confidence: 99%
“…Further study found this annotation came from pregnancy specific glycoprotein (PSG) 1, 4, 5, 6, 7, 9, 11. Among them, PSG9 was found to be upregulated in the early stage of colorectal cancer (CRC), and drives the progression of CRC and tumor angiogenesis 10,11. In pancreatic adenocarcinoma, cytoplasmic localized PSG1 is associated with shortened median survival 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we previously identified PSG9 that directly binding to SMAD4 and promoted its nuclear translocation, subsequently activation genes expression associated with angiogenesis. 25 Usually, SMAD1/5/9 and SMAD2/3 existed as complexes and conducted canonical and mixed TGF-b/BMP signaling respectively in cytoplasm. 26 In addition, phosphorylated SMAD1/5/9 and SMAD2/3 complexes were distributed in nucleus.…”
Section: Discussionmentioning
confidence: 99%